National identity and conversion through medieval romance : The case of Hrafn Gunnlaugsson's film "Í skugga hrafnsins" (In the shadow of the raven) - Chance, Jane; Weinstein, Jessica (Universität Tübingen, 2004)
Blending elements of Icelandic saga (Njal's Saga, Laxdaela Saga) and late medieval Arthurian romance (the Icelandic version of the Tristan legend), director Hrafn Gunnlaugsson troubles the question of heroic allegiance in relation to national identity, religion (Christianity as opposed to belief in the northern gods), and romantic love through the family feud of his hero Trausti in "I skugga Hrafnsins." That is, Trausti returns to Iceland from training in Norway as a priest to assume the role of head of his family, which is embroiled in a conflict with another clan over a dead whale; his adversary in the dispute is Isold, daughter of Erikur and unmarried mother pledged to the son of the bishop of Iceland. The priority of conflicting claims – the pagan heroic code of vengeance, familial obligation, and fate versus Christian mercy, obligation to God, and individual will – is traced against a backdrop of claims of national identity versus the monolithic blurring of boundaries demanded by the dominance of the Church. All of the issues, conventionally debated in the Middle Ages within the genre of the saga on the one hand and the romance on the other, are complicated in the film by the romance's courtly-love context of attraction of mortal enemies Isold and Trausti. The inversion of the two genres within a contemporary film (1988) provides a uniquely Icelandic perspective on the relationship of the present to tradition, history, and the past – and the probing question of boundaries and transgressions, for the individual and for nation.